If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 = 11x + -27 Reorder the terms: -5 + 3x = 11x + -27 Reorder the terms: -5 + 3x = -27 + 11x Solving -5 + 3x = -27 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -5 + 3x + -11x = -27 + 11x + -11x Combine like terms: 3x + -11x = -8x -5 + -8x = -27 + 11x + -11x Combine like terms: 11x + -11x = 0 -5 + -8x = -27 + 0 -5 + -8x = -27 Add '5' to each side of the equation. -5 + 5 + -8x = -27 + 5 Combine like terms: -5 + 5 = 0 0 + -8x = -27 + 5 -8x = -27 + 5 Combine like terms: -27 + 5 = -22 -8x = -22 Divide each side by '-8'. x = 2.75 Simplifying x = 2.75
| 7(-4+2)= | | 3*2-14=a | | Y=16x+10 | | 6x+26=16x-74 | | 2h+g+4h= | | 2(3-2x)=x-4 | | 6a-4a+5=8-2a | | (3+7i)-(5-2i)= | | 6a+3a-5=7a-23 | | 9+12i= | | 6(x+3)=2(3x+5)+8 | | 2p+12=60 | | 4y+10=6y+2 | | 6(x+3)=6(x+8) | | 10x+0=10 | | 49x^2+64=0 | | 8a-6=3a+20 | | 36=x^2 | | X+X+2Y=4 | | 7x+2y=24 | | 19=-3x+7 | | 13x+11y=-19 | | -20=2(u+5)-8u | | -6(x-18)+3(x+3)=x+14 | | -4x+4=-8 | | 48a^2-16=0 | | -4+4=-8 | | 4w^2+27w+35=0 | | -x+1+9x=-3+4x+24 | | 3s^2+19s+28=0 | | -(4x+4)-(-3x-7)=-2 | | 16=-13x+3 |